The Implementation of Tarbiyah Science in Character Building in Early Childhood at TAUD SaQu Arinal Haq Bandung - Syahrial, Ghina Saniyah; Syaodih, Ernawulan; Mariyana, Rita (GoAcademica Research & Publishing, 2025)
This paper discusses the implementation of the concept of Tarbiyah in the formation of early childhood character at TAUD SaQu Arinal Haq Bandung. The background of this research departs from the phenomenon of declining values of politeness, empathy, and increasing aggressive behavior in society, so that educational intervention is needed during the golden age (0–6 years) as a crucial phase of character formation. This study uses a descriptive qualitative approach with the subjects of school principals, teachers, and students. Data was collected through observation, interviews, and documentation. The results of the study show that the implementation of Tarbiyah is carried out through routine activities such as greetings and prayers, daily dhikr, congregational Dhuha prayers, the use of thayyibah sentences, recitations of the Qur'an with the At-Tibyan method, as well as learning aqidah and fiqh. This practice is effective in fostering discipline, responsibility, empathy, and love for the Qur'an and Islamic teachings. Thus, Tarbiyah has proven to play a fundamental role in shaping children's character and personality holistically through habituation of Islamic behavior and exemplary in a religious and fun learning environment